PPP Policy, Depoliticisation, and Anti-Politics - Tom Willems (Coordinamento SIBA, 2017)
This article disentangles the complex relationship between depoliticisation and anti-politics in public-private partnership (PPP) policies and practices. By identifying three social mechanisms that underlie dynamics of depoliticisation in PPPs, namely consultocracy, yield bias, and complex contracting, it contrib-utes to the growing interdisciplinary literature on depoliticisation. The article argues that as depoliticisation continues to evolve, it further increases the unbalance between depoliticisation and politicisation, which has negative implications for democratic governance. The depoliticised logic behind PPPs feeds broad sen-timents of political distrust and disappointment, because political decision makers tend to use PPPs as mir-acle solutions for the delivery of public infrastructure without bearing the long-term budgetary conse-quences of their own decisions. This constitutes an expectations gap: the difference between what is prom-ised or expected by politicians on the one hand, and what they can actually deliver on the other. It is here that the short-term rationales and incentives of political decision makers collide with the wider public inter-est in the longer term.